PENGEMBANGAN METODE IN SILICO UNTUK KAJIAN AWAL KEAMANAN BAHAN TAMBAHAN PANGAN PADA RESEPTOR SEROTONIN - Hikmah, Bill
The development of new potential compounds as food additives is currently very rapid. However, these compounds must be safe for consumption and do not stimulate any biological activities in the body. Therefore, a rapid test method is needed to predict the safety of the compounds. A Safety evaluation that can be developed is a study of the interactions between food additives and receptors in the body. One of the important receptors in the body is serotonin, which works in various physiological functions, such as in the cardiovascular and gastrointestinal systems. This research conducted the development of in silico method including docking and molecular dynamics simulations of food additives (flavoring agents, antioxidants, sweetener, preservatives, and food coloring agents) against the 5?HT2B receptor (PDB ID: 5TVN), with references based on drugs that are evidently known for their affinity and effectiveness againts the receptor. The results of docking simulation are sorted and clustered, then the top 5 food additives from each category are selected as samples for the molecular dynamics simulation. The evaluation of interaction stability of each food additive againts the receptor was assessed based on molecular dynamics simulation. The overall results revealed, 18 compounds were predicted to be potentially safe, while seven others were predicted to be potentially unsafe. This evaluation method was validated using data from the Joint FAO/WHO Expert Committee on Food Additives(JECFA).